A preliininary study of p53 exon 8 tumour suppressor gene and ret/ptc 1 oncogtne in multinodular goiter of thyroidectomized patients in HUSM - Othman, Nor Hayati (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Malignant changes could be influenced by mutated product o£ Oncogene (i.e.. TIPTC) and Tumour suppressor gene